The Influence of Leadership Style, Discipline, and Motivation on the Performance of Civil Servants in the Army Headquarters - Ulung Dimas; Mochamad Vrans Romi (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
Civil servants (PNS) in military organizations play a vital role in national security. They fulfill their primary duties in accordance with their assigned class and position. TNI civil servants are essential for the execution of TNI duties, serving as a necessary complement to TNI soldiers. The collaboration between military personnel and PNS is crucial for the successful fulfillment of official responsibilities. Nevertheless, preliminary observations and interviews conducted revealed a decline in the performance of public workers from 2018 to 2021. This decline can be attributed to factors such as civil servants breaching disciplinary standards and experiencing poor levels of employee morale. The objective of this study is to analyze the impact of leadership style, work discipline, and work motivation on the performance of civil servants at the TNI-AD Headquarters. This study employed quantitative research methodologies and focused on government servants at the TNI-AD Headquarters. The sample size consisted of 90 respondents, selected using a simple random sampling procedure. The data was analyzed using SPSS 25, which included conducting validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using T-tests and F-tests. The findings indicate that leadership style, work discipline, and work motivation exert a favorable and substantial impact on the performance of PNS Indonesian Army Headquarters.